Clinical Presentation of Severe Viral Encephalitis With Known Causative Agents in Children: A Retrospective Study on 16 Patients Hospitalized in a Pediatric Intensive Care Unit (2008-2011). (November 2014) - Adenot, Marc; Frobert, Emilie; Blanchard, Gaëlle; Morel, Benoit; Perrot, Laurence; Floret, Daniel; Javouhey, Etienne
A retrospective analysis was conducted in a French pediatric hospital in Lyon. Subjects were 16 patients diagnosed with acute viral encephalitis with identified causative agents who were admitted to the pediatric intensive care unit from 2008 to 2011. The median length of stay was 6 days. The outcome was favorable for 77% of the patients. Analysis of biological and clinical findings based on causative agents did not reveal clinical patterns or neurological findings specific to the causal viruses. Nevertheless, uncommon clinical pictures and severe neurological complications were highlighted, in particular for children with influenza-related encephalitis and herpes simplex encephalitis. This case series exemplifies the difficulties, even pitfalls, in establishing a diagnosis of encephalitis, especially in neonates. It points out significant differences in the clinical presentation of encephalitis in children compared with clinical pictures described in previously published large-scale studies on encephalitis mainly conducted in adults.